Faecal haemoglobin concentration predicts all-cause mortality. (May 2023) - Deding, Ulrik; Kaalby, Lasse; Steele, Robert; Al-Najami, Issam; Kobaek-Larsen, Morten; Plantener, Eva; Madsen, Jeppe B.; Madsen, Jonna S.; Bjørsum-Meyer, Thomas; Baatrup, Gunnar
Abstract: Background: Population-based screening for colorectal cancer by a faecal immunochemical test (FIT) is recommended by the European Union. Detectable faecal haemoglobin can indicate colorectal neoplasia as well as other conditions. A positive FIT predicts an increased risk of death from colorectal cancer but might also predict an increased risk of all-cause mortality. Methods: A cohort of screening participants was followed using the Danish National Register of Causes of Death. Data were retrieved from the Danish Colorectal Cancer Screening Database supplemented with FIT concentrations. Colorectal cancer specific and all-cause mortality were compared between FIT concentration groups using multivariate cox proportional hazards regression models. Findings: In 444, 910 Danes invited for the screening program, 25, 234 (5·7%) died during a mean follow-up of 56·5 months. Colorectal cancer caused 1120 deaths. The risk of colorectal cancer death increased with the increasing FIT concentration. The hazard ratios ranged from 2·6 to 25·9 compared to individuals with FIT concentrations <4 μg hb/g faeces. Causes other than colorectal cancer caused 24, 114 deaths. The risk of all-cause death increased with the increasing FIT concentration, with the hazard ratios ranging from 1·6 to 5·3 compared to individuals with FIT concentrations <4 μg hb/g faeces. Interpretation: The risk of colorectal cancer mortality increased with the increasing FIT concentrations even for FIT concentrations considered negative in all European screening programs. The risk of all-cause mortality was also increased for individuals with detectable faecal blood. For colorectal cancer specific mortality and all-cause mortality, the risk was increased at the FIT concentrations as low as 4–9 μg hb/g faeces. Funding: The study was funded by the Odense University Hospital grants A3610 and A2359. Highlights: A dose–response relationship between faecal immunochemical test (FIT) level and all-cause mortality was found. The same was evident for colorectal cancer mortality. Excess mortality from increased FIT levels is more than twentyfold from non-colorectal cancer causes. A fixed screening interval of two years between negative FITs may not be efficient. Determining the interval by the FIT level may increase the yield of screening.